PROFILE OF THE NEED FOR GAMIFICATION-BASED CHEMISTRY LEARNING MEDIA FOR MENTALLY RETARDED STUDENTS IN IMPROVING THE QUALITY OF LEARNING - Rokhim, Deni Ainur; Nenohai, Jacky Anggara; Agustina, Nur Indah; Putra, Moch Chesa Nur Hidayat Arif; Amalia, Firda; Munzil, Munzil (Jurusan Pendidikan Luar Biasa, 2022)
Mental retardation is a child who experiences obstacles in mental development or intelligence. This study aims to analysis the need for gamification-based chemistry learning media for mentally retarded students. The research method used is a qualitative survey method. The data collection process was carried out by distributing research questionnaires to 3 teachers and 12 students at the Sidoarjo Regency Inclusive Senior High School. The results showed that mentally retarded students needed gamification-based chemistry learning media. This is because gamificationbased chemistry learning media has elements of images, videos, and games in it so that it can make mentally retarded students more active in the learning process, and can attract mentally retarded students' interest in studying chemistry at school.